Perhitungan Jumlah Bahan Bakar LPG Dan Minyak Tanah Di Wilayah Pengembangan (WP)-V Kota Pekanbaru - Rosyanti, Vasella Dwi; Sasmita, Aryo; Asmura, Jecky (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Development Area V is the most densely populated area with an area of 32% from Pekanbaru City. Based on BPS (2017), the area Development V 140,96 km2 consists of 3 subdistricts, Tampan District, Marpoyan Damai, and Payung Sekaki. Population growth in this region is influenced by several factors, residential areas, higher education centers, city government office buildings and hospitals (RPJMD Pekanbaru, 2017-2022). The high number of residents in WP V with a variety of population activities will certainly have an effect on the resulting CO2 emissions. This research will be conducted on the calculation of the amount of CO2 emissions with IPCC (1996) method from household activities. The primary carbon emissions related to fuel use. Based on the calculation results, it was found that the primary CO2 emissions from fuel use generated in WP V Kota Pekanbaru is 3.136,1 ton CO2/month. Keywords: Household, fuel use, primary CO2 emissions